Algae: A potential feedstock for third generation biofuel. (2022) - Sachin Powar, Ranveer; Singh Yadav, Anil; Siva Ramakrishna, Ch.; Patel, Swastika; Mohan, Man; Sakharwade, Sanjay G; Choubey, Mayank; Kumar Ansu, Alok; Sharma, Abhishek
Abstract: Due to increase in population and augmented usage of conventional fuels; raised interest among scientist to find some potential substitute of conventional fuels for sustainable development, because these fuels are limited and also non-renewable. Many alternative fuels such as biodiesel, ethanol, methanol, synthetic fuels, hydrogen, biogas, natural gas, etc. have been used as internal combustion (IC) engines fuels. Liquid biofuels gained lot of attention as alternative to fossil fuels because it can be derived from renewable biomass resources. The first-generation biofuels originate dispute over food versus fuel as most of the feedstocks are edible. In this regard, algae have emerged as a vital source of production of third generation biofuels, such as bioethanol, biohydrogen, biopropane etc. In some cases the oil yield from microalgae are better as compared to several oil producing crops. Microalgae are photosynthetic microorganisms which convert sunlight, water, and carbon dioxide to sugars, from which macromolecules, such as lipids and triacylglycerols can be obtained. In this paper, the detailed information about algae, its cultivation techniques and lipid extraction for the production of biofuels have been discussed. The characterization of the fuel obtained by algae and its application as diesel engine fuel have also covered in this paper.